Effects of six weeks of plyometric training on the ground vs on a mini-trampoline on strength, jump performance, and balance in male basketball players—randomized clinical trial - Villalba, M. M.; Eltz, G. D.; Fujita, R. A.; Panhan, A. C.; Cardozo, A. C.; Gonçalves, M. (Sport Sciences for Health, 2023)
Purpose To compare the effects of a 6-week plyometric training protocol performed on the ground or a mini-trampoline on basketball players' strength, jumping, landing, and balance.